Synthesis of chiral S, N-thioimidazoline ligands for palladium-catalyzed asymmetric allylic alkylations. Issue 4 (15th March 2016) - Hao, Xin-Qi; Shen, Ming-Zhan; Jian, Ning-Ge; Pang, Wei; Shen, Xiao-Jing; Zhu, Xinju; Song, Mao-Ping
Graphical abstract: Abstract: A series of chiral S, N -thioimidazoline ligands have been synthesized using 2-bromobenzoic acid or 1-bromo-2-naphthoic acid as starting materials. The obtained ligands were evaluated in the Pd-catalyzed asymmetric allylic alkylations and exhibited high catalytic efficiency: yields of up to 94% and enantioselectivities of up to 86% were achieved under the optimized conditions. Abstract : ( S )-2-(2-Bromophenyl)-4-isopropyl-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C19 H21 BrN2 [ α ]D 20 = −92 ( c 1.22, CH2 Cl2 ) Absolute configuration: ( S ) Abstract : ( S )-2-(2-Bromophenyl)-4-phenyl-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C22 H19 BrN2 [ α ]D 20 = −131 ( c 1.70, CH2 Cl2 ) Absolute configuration: ( S ) Abstract : ( S )-2-(1-Bromonaphthalen-2-yl)-4-( tert -butyl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C24 H25 BrN2 [ α ]D 20 = −14 ( c 0.19, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-( tert -Butyl)-2-(2-(phenylthio)phenyl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C20 H23 BrN2 [ α ]D 20 = −48 ( c 1.10, CH2 Cl2 ) Absolute configuration: ( S ) Abstract : ( S )-2-(1-Bromonaphthalen-2-yl)-4-isopropyl-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C23 H23 BrN2 [ α ]D 20 = −49 ( c 0.22, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-2-(1-Bromonaphthalen-2-yl)-4-phenyl-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C26 H21 BrN2 [ α ]D 20 = −156 ( c 0.11, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-Isopropyl-2-(2-(phenylthio)phenyl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C25 H26 N2 S [ α ]D 20 = −37 ( c 0.48, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-Phenyl-2-(2-(phenylthio)phenyl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C28 H24 N2 S [ α ]D 20 = −76 ( c 0.71, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-Isopropyl-2-(1-(phenylthio)naphthalen-2-yl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C29 H28 N2 S [ α ]D 20 = −4 ( c 0.41, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-Phenyl-2-(1-(phenylthio)naphthalen-2-yl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C32 H26 N2 S [ α ]D 20 = −108 ( c 0.65, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-4-( tert -Butyl)-2-(2-(phenylthio)phenyl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C26 H28 N2 S [ α ]D 20 = −18 ( c 0.50, CHCl3 ) Absolute configuration: ( S ) Abstract : ( S )-2-(2-(Isopropylthio)phenyl)-4-phenyl-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C25 H26 N2 S [ α ]D 20 = −64 ( c 0.1, CH2 Cl2 ) Absolute configuration: ( S ) Abstract : ( S )-4-( tert -Butyl)-2-(1-(phenylthio)naphthalen-2-yl)-1-( p -tolyl)-4, 5-dihydro-1 H -imidazole: C30 H30 N2 S [ α ]D 20 = +31 ( c 0.53, CHCl3 ) Absolute configuration: ( S )